Efficacy and Safety of Insulin Protocol among Medical and Surgical Patients Admitted in the Medical City Hospital - Adorable-Wagan, Perie; Paz-Pacheco, Elizabeth; Aligui, Gemiliano (Journal of the ASEAN Federation of Endocrine Societies, 2014)
Objectives. The general objective was to compare the efficacy and safety of the Markovitz insulin protocol (MIP) with physician directed insulin infusion (PDI). Specific objectives were to compare the rate of change to normal glucose levels between MIP and PDP, time to achieve normal glucose levels and to determine the number of hypoglycemic episodes between MIP and PDI. Methodology. This is a retrospective study examining the medical records of critically ill patients admitted from 2001-2009. Efficacy outcome was measured as the time to achieve normal glucose level and the mean difference of percentage change towards normal blood glucose level. Safety outcome was measured in terms of frequency of hypoglycemic episodes. Results. One hundred and one patients met the inclusion criteria. The mean time required to achieve target blood glucose levels was 24 hrs (SD=19.5) for MIP compared to PDI. The mean drop in blood glucose levels was -235.49 (SD=113.4), with mean percent difference of -57.5% (SD=20.72) (p-value = 0.919) for MIP compared to physician directed. The MIP resulted in a higher percentage of blood glucose within target (19.57% vs 9.86 %) compared to PID (p= 0.005). Patients in MIP had shorter ICU stay (p=0.049). In addition, MIP was associated with a significantly lower rate of hypoglycemia at 4.2%, compared to PID at 30% (p<0.001). Conclusions. Markovitz insulin protocol appeared to be significant to physician directed insulin infusion in terms of its greater percentage of glucose measurements maintained within target range, without an increased risk of severe hypoglycemia.